Respostas
respondido por:
5
Diagonal principal
[-1 . (x+4) . x ] + [ 3 . x . 1] + [ -2 . 0 . 1]
[ -1 . ( x² + 4x)] + 3x + 0
- x² - 4x + 3x
- x² - x
Diagonal secundária
[1. 1. (x+4)] + [ 3. - 2 . x ] + [ x . 0 . -1]
x + 4 - 6x + 0
- 5x + 4
Dp - Ds = 0
( - x² - x ) - ( - 5x + 4) = 0
- x² - x + 5x - 4 = 0
- x² + 4x - 4 = 0
x' = -4/ -2 = 2
tokugawamasamune:
Muito obrigado!!
respondido por:
0
Resposta:
X'=-4/-2=2 valeu mano tamo junto
Perguntas similares
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás